2023
DOI: 10.3390/molecules28020650
|View full text |Cite
|
Sign up to set email alerts
|

Visible-Light-Enhanced Antibacterial Activity of Silver and Copper Co-Doped Titania Formed on Titanium via Chemical and Thermal Treatments

Abstract: Dental implants made of titanium (Ti) are used in dentistry, but peri-implantitis is a serious associated problem. Antibacterial and osteoconductive Ti dental implants may decrease the risk of peri-implantitis. In this study, titania (TiO2) co-doped with silver (Ag) at 2.5 at.% and copper (Cu) at 4.9 at.% was formed on Ti substrates via chemical and thermal treatments. The Ag and Cu co-doped TiO2 formed apatite in a simulated body fluid, which suggests osteoconductivity. It also showed antibacterial activity a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…The chemical composition of the implant surface can influence the adhesion of proteins and bacteria ( Yu et al, 2022 ). Therefore, proper modification of titanium surface to inhibit bacterial adhesion and growth is a method worth considering ( Suzuki et al, 2023 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The chemical composition of the implant surface can influence the adhesion of proteins and bacteria ( Yu et al, 2022 ). Therefore, proper modification of titanium surface to inhibit bacterial adhesion and growth is a method worth considering ( Suzuki et al, 2023 ).…”
Section: Resultsmentioning
confidence: 99%
“…Implant restoration has become a crucial method for replacing missing teeth due to its excellent function and aesthetic effects ( Jiang et al, 2020 ; Li et al, 2022b ). However, 42%–43% patients will suffer from peri-implant mucositis after oral implant restoration, and 20%–22% patients will suffer from peri-implantitis ( Lee et al, 2017 ; Onclin et al, 2022 ; Suzuki et al, 2023 ). What is more concerning is that peri-implant mucositis can further develop into peri-implantitis ( Herrera et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…Many researches have been reported to extend the excitation spectrum of TiO 2 to visible light range by incorporating other elements. [32][33][34]43,151,152 Suzuki et al 33 fabricated Cu-dopped TiO 2 by alkali and heat treatment in copper nitrate and verified that the Cu-dopped TiO 2 exhibited antibacterial properties by generating hydroxyl radicals under visible light (460 nm) irradiation. Additionally, Xu et al 37 reported a visible lighttriggered drug release platform by decorating gold nanoparticles (AuNPs) with TNTs using a bio-templated method.…”
Section: Enzymesmentioning
confidence: 99%
“…Under UV or visible light illumination for 20 minutes, negative or positive charges were accumulated on the Gr/TN film respectively, which changed the conformation of extracellular matrix (ECM) molecules to a more disordered state, ultimately resulting in cell detachment. 68 However, limited studies on the in situ UV light-responsive strategy were little more than in vitro cell (1) Photocatalysis producing ROS (PDT) (1) PDT and/or PTT for antibacterial or anti-tumor applications 23,26,30,[39][40][41][42][43][44][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62]66,69 (2) Incorporating photosensitive molecules (PDA, RP, IR780 and etc.) 23,30,39, (2) Photo-triggered hyperthermia (PTT)…”
Section: Photostimulation-responsive Strategiesmentioning
confidence: 99%
“…Various studies have used some of transition metals (Fe, Cu, Ce, and Au) or non-metals (N, B, S, and F) as dopant for titania , which leads to increase in its visible light absorption capacity 14 – 16 . Based on studies conducted, it has been determined that copper (Cu) and nitrogen (N) ions serve as appropriate dopants for titania when used at optimal concentrations 17 , 18 . These dopants play a vital role in activating surface sites, reducing the recombination rates of electrons and holes, and narrowing the band-gap of titania 14 , 18 .…”
Section: Introductionmentioning
confidence: 99%